Calculation of Hypocentral Parameters using the Generalized Inversion Method - Jiménez, César (2017)
In this research a generalized inversion method was applied to obtain the epicenter of seismic events of local and regional origin from the readings of arrival time of P and S phases of at least 4 seismic stations. The initial condition of the model is obtained from the location of the seismic station closest to the epicenter, the initial origin time is obtained from the Wadati diagram and the initial depth is set up to 33 km for each case. We suppose a homogeneous velocity model of the P wave of 7.6 km/s (obtained from the inversion process). From the analysis of eigenvalues and eigenvectors of the system matrix (GTG), we deduce that the most stable parameter is the origin time and the most unstable parameter is the focal depth. The linearized model converges quickly to the solution.